2019
DOI: 10.3390/s19143182
|View full text |Cite
|
Sign up to set email alerts
|

Sub-ppm Formaldehyde Detection by n-n TiO2@SnO2 Nanocomposites

Abstract: Formaldehyde (HCHO) is an important indicator of indoor air quality and one of the markers for detecting lung cancer. Both medical and air quality applications require the detection of formaldehyde in the sub-ppm range. Nanocomposites SnO2/TiO2 are promising candidates for HCHO detection, both in dark conditions and under UV illumination. Nanocomposites TiO2@SnO2 were synthesized by ALD method using nanocrystalline SnO2 powder as a substrate for TiO2 layer growth. The microstructure and composition of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 120 publications
(166 reference statements)
0
23
0
Order By: Relevance
“…The second wide band at 563 cm −1 is associated with in-plane oxygen vacancies of the nanocrystalline SnO 2 [40][41][42]. The bands at 309 and 352 cm −1 and the band at 444 cm −1 are assigned to the E u and B 1u modes, respectively, associated with transformation of an IR to Raman active modes [43]. In2O3, bixbyite 7 ± 1 7 ± 2 90 ± 5 3-4 (a) crystallite size from XRD; (b) particle size from TEM; (c) specific surface area.…”
Section: Characteristics Of Nanocrystalline Semiconductor Oxidesmentioning
confidence: 97%
See 1 more Smart Citation
“…The second wide band at 563 cm −1 is associated with in-plane oxygen vacancies of the nanocrystalline SnO 2 [40][41][42]. The bands at 309 and 352 cm −1 and the band at 444 cm −1 are assigned to the E u and B 1u modes, respectively, associated with transformation of an IR to Raman active modes [43]. In2O3, bixbyite 7 ± 1 7 ± 2 90 ± 5 3-4 (a) crystallite size from XRD; (b) particle size from TEM; (c) specific surface area.…”
Section: Characteristics Of Nanocrystalline Semiconductor Oxidesmentioning
confidence: 97%
“…The second wide band at 563 cm −1 is associated with in-plane oxygen vacancies of the nanocrystalline SnO2 [40][41][42]. The bands at 309 and 352 cm −1 and the band at 444 cm −1 are assigned to the Eu and B1u modes, respectively, associated with transformation of an IR to Raman active modes [43]. Characteristic Raman vibrational modes corresponding to the body-centered cubic In2O3 are observed at 132, 307.7, 366.7, 494.6, and 628.5 cm −1 and their positions are in agreement with previously reported data [44][45][46].…”
Section: Characteristics Of Nanocrystalline Semiconductor Oxidesmentioning
confidence: 98%
“…Due to the suitable combination of chemical and semiconducting properties, TiO 2 has catalytic activity and even photocatalytic activity, both of which can be expressed by the 'water splitting ability' or 'oxidational activity'; these phenomena significantly strengthen when the sensing TiO 2 structure is irradiated by UV light [44,71]. It was demonstrated that the pulsed laser modification can be successfully employed as a large-scale method to enhance the electronic properties of TiO 2 nanotubes and such a structure can contribute to the improved photocatalytic or photovoltaic performance of these TiO 2 nanotubes [72]. Therefore, the additional application of catalytic activity in TiO 2 -based gas and VOC sensors is foreseen; however, it is still rarely exploited, due to significant complexity in operation of such structures.…”
Section: Strategies To Reduce Energy Consumption In Gas and Voc Sensorsmentioning
confidence: 99%
“…Therefore, the additional application of catalytic activity in TiO 2 -based gas and VOC sensors is foreseen; however, it is still rarely exploited, due to significant complexity in operation of such structures. TiO 2 has been used as a sensing material in room-temperature sensors for formaldehyde [72,73], ozone [45], O 2 [68], CO [46], C 7 H 8 [47], ethanol [65,67,74], H 2 [75,76], and some other gases and VOCs [77].…”
Section: Strategies To Reduce Energy Consumption In Gas and Voc Sensorsmentioning
confidence: 99%
“…For formaldehyde, we tested two mature technologies, namely, electrochemical and colorimetric, for TVOC, MOS, and PID. We know that other technologies based on nanomaterials exist but they are still in the research stage [21,22].…”
mentioning
confidence: 99%